Adiponutrin and Adiponectin Gene Variants in Indonesian Patients with Non-Alcoholic Fatty Liver Disease: a Preliminary Study - Rayvita AN Meagratia; Ferdy Kurniawan Cayami; Udin Bahrudin; Wiwik Lestari; Nani Maharani; Sultana MH Faradz; Hery Djagat Purnomo (Journal of Biomedicine and Translational Research, 2021)
BackgroundVariants of adiponutrin (PNPLA3) and adiponectin (ADIPOQ) genes were considered to be associated with non-alcoholic fatty liver disease (NAFLD). Although the prevalence of NAFLD is increasing, there are limited numbers of studies about the association in Indonesian population.ObjectiveTo confirm whether specific variants of adiponutrin (PNPLA3) and adiponectin (ADIPOQ) genes are associated with NAFLD in Indonesian patients.MethodsData and DNA of 152 participants were obtained from a previous study in Dr. Kariadi Hospital, Semarang, Indonesia. PCR-RFLP analysis was performed for detection of PNPLA3 rs738409 and ADIPOQ rs2241767 variants. The diagnosis and severity of NAFLD were assessed according to NAFLD activity score (NAS) based on histopathology assessment of liverbiopsy.ResultsAllele G of PNPLA3rs738409 was associated with NAFLD in both bivariate (p=0.009, OR 2.52, CI 95% 1.25–5.07) and multivariate (p=0.008, OR 2.62, CI 95% 1.29%–5.32%) analysis, while ADIPOQ rs2241767 had no significant association. In NAFLD participants, both genotypes showed allele G was higher in the group of possible non-alcoholic steatohepatitis (NASH) – NASH (NAS >2) than in the simple steatosis group (NAS <2) i.e. 40.0% vs. 3.75% for the rs2241767 variant and 23.75% vs. 1.25% for the rs738409 variant, without significant association.ConclusionVariant PNPLA3 rs738409 was associated with NAFLD incidence in studied population. Among NAFLD participants, the frequency of both variants were found higher in the possible NASH – NASH group, yet needs to be confirmed with more participants and a multicenter study.Data and DNA of 152 participants were obtained from a previous study in Dr. Kariadi Hospital, Semarang, Indonesia. PCR-RFLP analysis was performed for detection of PNPLA3 rs738409 and ADIPOQ rs2241767 variants. The diagnosis and severity of NAFLD were assessed according to NAFLD activity score (NAS) based on histopathology assessment of liverbiopsy.